Sequências didáticas para o ensino de matemática em nível fundamental: análise da influência de um curso de capacitação fundamentado no conceito de registros de representação semiótica - Costa, Jeanine Ferreira dos Anjos (2009)
Considering internal didactic transposition processes of Chevallard (1991), and ethnomathematics approach of D’Ambrosio (2001), in this case study, the influence of a training course based on the concepts of semiotic representation registers of Duval (1993) is verified on the proposition of teaching sequences applicable to math teaching for 5th grade students of a school in a city of the region of Amurel, SC, which works with students from rural communities. The sequences produced in post-test by two groups of four teachers showed progress with regard to consciousness: of the importance of the contextualization of teaching objects; of the use of three cognitive activities proposed by Duval (1993), with emphasis on the conversion of registers of representation; and of the distinction between noesis and semiosis. However, the sequences were thought as applicable to the own teachers instead to be applicable to the 5th grade students. These results show that the teachers did not distinguish mathematical objects and concepts of their representations, pointing to the need of investing in this topic in teaching training